Post and long-COVID conditions: Epidemiology, clinical symptoms and the prevention and treatment - Pooja Chauhan; Vineet Kumar Pathak; Dewesh Kumar; Anita Upadhyay; Anirban Chatterjee; Chandrakant Lahariya (Journal of Medical Evidence, 2022)
A proportion of individuals affected with severe acute respiratory syndrome coronavirus 2 continue to have COVID-19 symptoms even after recovering from illness. These are termed as post-COVID condition (PCC)/long-COVID. Evidence suggests that symptoms of COVID-19 along with other generalised sequelae may persist in some patients with severe and very severe disease, as well as in patients who had mild or no symptoms. The management of PCC is a challenge as there is limited understanding about the issue even in healthcare professionals. Then, there is not enough documentation of post-COVID and long-COVID in India. From public health perspective, the health services and facilities have not been re-designed to tackle the situation. This review article aims to explore PCC and compilation of current international and national public health response along with recommendations to identify and manage the PCC at the primary. The article concludes the urgent need to document the burden of PCCs in India, develop standard case definition and equip primary healthcare facilities and providers with the requisite skills to manage the PCC. The governments, health care providers and facilities and public health bodies should also encourage and foster continuing country specific data, analysis and research into the determinants, duration and probable treatment modalities of PCC. The post and long-COVID conditions would require sustained policy and programmatic attention in all countries with special focus in low and middle income country settings.